2023
DOI: 10.1088/1402-4896/acc0e4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dislocations on ionic conductivity and dendrite formation in solid electrolytes

Abstract: In order to study the recently proposed strategy to tailor the electrical property of ceramics by the introduction of dislocations, numerical calculations are performed on the influence of parallel straight dislocations on ionic conductivity and dendrite formation in single-crystal solid electrolytes. If the diameter of a dislocation pipe is more than root(2) times larger than the distance between neighboring dislocations, the ionic current density is nearly uniform on the electrode and the dendrite formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 68 publications
0
27
0
Order By: Relevance
“…Indeed, Wang et al [35] experimentally reported the dislocation density as high as 10 18 m −2 in single-crystal ceramics (alumina) by high-temperature laser shock peening in 2021. Accordingly, the theoretically predicted increase in ionic conductivity by 6 or 7 orders of magnitude without dendrite formation by introducing parallel straight dislocations into single-crystal solid electrolytes with the dislocation density higher than about 10 17 m −2 may be practically possible [24]. Although the numerical curves in figures 2 and 4 are shifted to higher or lower dislocation densities for ceramics with higher or lower compressive strength, respectively, the qualitative conclusion is unaffected.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Indeed, Wang et al [35] experimentally reported the dislocation density as high as 10 18 m −2 in single-crystal ceramics (alumina) by high-temperature laser shock peening in 2021. Accordingly, the theoretically predicted increase in ionic conductivity by 6 or 7 orders of magnitude without dendrite formation by introducing parallel straight dislocations into single-crystal solid electrolytes with the dislocation density higher than about 10 17 m −2 may be practically possible [24]. Although the numerical curves in figures 2 and 4 are shifted to higher or lower dislocation densities for ceramics with higher or lower compressive strength, respectively, the qualitative conclusion is unaffected.…”
Section: Resultsmentioning
confidence: 84%
“…With regard to diffusion coefficient of ions which is proportional to ionic conductivity in solid electrolyte, it is several orders of magnitude higher along dislocations compared to that in the bulk solid [3,[24][25][26][27]. Accordingly, it is expected that ionic conductivity increases considerably by introducing appropriate dislocations in solid electrolyte [3-5, 20, 24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For each straight dislocation, a dislocation pipe is considered along which ionic conductivity is significantly higher than that in the bulk because the concentration of vacancies is considerably higher [59][60][61][62]. The typical diameter of a dislocation pipe is denoted by 𝛿, and the distance between neighboring dislocations is denoted by 𝑑 which is given by Equation ( 31) [57]:…”
Section: Ionic Conductivity In Solid Electrolytesmentioning
confidence: 99%
“…Under the condition of all-dislocation-ceramics, the ionic current density is spatially uniform and the mean ionic conductivity could be seven orders of magnitude larger than that in the bulk (Figure 17) [57]. Below the critical dislocation density, on the other hand, dendrite formation may be inevitable because the ionic current is concentrated along dislocations (Figure 17) [57]. Recently, it has been suggested that the introduction of dislocations is useful for improving the functional, electrical and mechanical properties of ceramics, which is called dislocation engineering [62][63][64][65][177][178][179][180].…”
Section: Ionic Conductivity In Solid Electrolytesmentioning
confidence: 99%